Answer:
PART A
g(R) =
;
PART B
g(R) = g(Rp) ×
.
Step-by-step explanation:
Given density of planet = rho.
The planet's radius = Rp.
An object is located a distance R from the center of the planet,
where R< Rp.
The gravitational fore between two point masses m₁ and m₂ is,
F =
; G= universal gravitational constant
r = distance between the masses.
for mass m₂ , F= m₂ g; where g = acceleration due to gravity;
so, g =
=
;
From figure, only inside part of the planet exerts force and which can be treated as a point mass.
so, g =
where
= mass of the planet with radius R.
⇒
= rho ×
×R³
⇒ g(R) =
→ PART A
PART B
At the surface g(Rp) =
⇒ g(R) = g(Rp) ×